Uniform random colored complexes. Issue 3 (8th March 2019) - Carrance, Ariane
Abstract : We present here random distributions on ( D + 1)‐edge‐colored, bipartite graphs with a fixed number of vertices 2 p . These graphs encode D ‐dimensional orientable colored complexes. We investigate the behavior of those graphs as p → ∞ . The techniques involved in this study also yield a Central Limit Theorem for the genus of a uniform map of order p, as p → ∞ .